Young and Older Adults' Gender Stereotype in Multitasking - Strobach, Tilo; Woszidlo, Alesia (Frontiers in Psychology, 2015)
In the present study, we investigated discrepancies between two components of stereotyping by means of the popular notion that women are better at multitasking behaviors: the cognitive structure in individuals (personal belief) and the perceived consensus regarding certain beliefs (perceived belief of groups). With focus on this notion, we examined whether there was empirical evidence for the stereotype’s existence and whether and how it was shared among different age groups. Data were collected from 241 young (n = 129) and older (n = 112) German individuals. The reported perceptions of gender effects at multitasking were substantial and thus demonstrated the existence of its stereotype. Importantly, in young and older adults, this stereotype existed in the perception of attributed characteristics by members of a collective (perceived belief of groups). When contrasting this perceived belief of groups and the personal belief, older adults showed a similar level of conformation of the gender stereotype while young adults were able to differentiate between these perspectives. Thus, young adults showed a discrepancy between the stereotype’s components cognitive structure in individuals and perceived consensus regarding certain beliefs.